Repositioning the Indonesian halal industry development strategy: SWOT and maqasid al-Sharia integration - Azwar, Azwar; Mulyawan, Andi Wawan; Siradjuddin, Siradjuddin; Parmitasari, Rika Dwi Ayu (International Journal of Halal Industry, 2026)
Purpose – This study aims to identify the strengths, weaknesses, opportunities, and threats that shape the development of the halal industry in Indonesia through the lens of maqasid al-Sharia. It also seeks to formulate strategic recommendations to reposition Indonesia’s halal industry for global competitiveness, while remaining grounded in Sharia values. Methodology – A mixed-methods approach with an exploratory sequential design was employed, combining qualitative findings from expert interviews and policy documentation with quantitative analysis through IFAS–EFAS weighting and strategic mapping using the internal-external (IE) matrix. Findings – The halal industry in Indonesia demonstrates major strengths, such as a vast domestic Muslim market, strong regulatory support, increasing halal awareness, abundant raw materials, and potential in halal tourism. However, it faces weaknesses, including inadequate infrastructure, limited human resource capacity, high certification costs, weak institutional coordination, and restricted global access. Externally, the industry benefits from rising global demand, digital transformation, and halal diplomacy but is challenged by intense competition, fragmented standards, and imported product penetration issues. Strategic mapping places Indonesia’s halal industry in a growth quadrant, requiring vertical integration strategies that cover halal supply assurance, human capital development, innovation, inclusive distribution, and global branding. Implications – The results provide practical insights for policymakers and stakeholders to design integrated, sustainable strategies that strengthen the competitiveness and inclusivity of Indonesia’s halal ecosystem in line with maqasid al-Sharia. Originality – This study uniquely integrates maqasid al-Sharia perspectives with strategic management tools to develop a holistic framework for sustainable and globally competitive halal industry development.